Analysis Factors of The Physical Environment on The Risk of Stunting in Pregnant Women - Suprihatin; Pebriyanti Putri, Rizka; Siauta, Jenny Anna (International Journal of Midwifery and Health Sciences, 2023)
Background: Stunting can occur before delivery due to inadequate nutrition during pregnancy, the causes of stunting also include social, physical, and biological environmental factors. Based onthe results of the study, it was found that 52 pregnant women in the second and third trimesters with high-risk pregnancies had the potential to give birth to children at risk of stunting. Purpose: This study aims to determine the relationship between physical environmental factorssuch as sanitation, clean water, family latrines, residential settings, and cigarette smoke pollutantswith the risk of stunting in the working area of the Batu City Health Center, Bogor Regency. Methods: This type of research is an analytic survey with a cross sectional approach. The research sample was 100 pregnant women. The research was conducted in September 2022 usinga questionnaire. Data analysis was performed univariately and bivariately using the Chi Squere statistical test. The frequency distribution of high-risk pregnant women is 52.0%, physicalenvironmental factors are not good sanitation is 68.0%, water is not clean 61.0%, does not have atoilet 55.0%, residential settings are at risk 55.0%, and cigarette smoke pollutants are 67.0%. Result: The results of statistical tests showed that there was a significant relationship between physical environmental factors and the risk of stunting with a p-value below 0.05. Conclusion: There is a significant relationship between sanitation, clean water, family latrines, residential settings, cigarette smoke pollutants with a high risk of pregnancy which has the potential for mothers to give birth to children at risk of stunting. It is expected to improve health education for pregnant women even before conception to create a superior generation free from stunting.